Learning Process at SMA Muhammadiyah Bangil During the Covid-19 Pandemic - Mustika Itsna Finurika; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to determine the online learning process at SMA Muhammadiyah Bangil during the Covid-19 pandemic, whether it is effective or not, as well as what difficulties teachers and students experience during the online learning process, then how do students respond to this online learning with using descriptive qualitative research methods with data collection techniques through interviews and observations with teachers at SMA Muhammadiyah Bangil with the result that the information needed is about the learning processin SMA Muhammadiyah Bangil during the Covid-19 pandemic, namely by using the online learning method. With the conclusion that the learning process at SMA Muhammadiyah Bangil uses an online learning system.